L-glutamine Supplemented Nutrition Alleviates Damage Caused by Corrosİve Esophagitis in Rats - Özkan Okur; Gülden Diniz; Oğuz Alp Arslan; Mehmet Can; Hüseyin Evciler; Akgün Oral; Münevver Hoşgör (Galenos Publishing House, 2022)
Objective: The primary goal in the treatment of corrosive esophagitis (CE) is to control inflammation and scar reactions. L-glutamine (Gln) is beneficial for the integrity of the intestinal mucosal epithelium and is an amino acid that promotes mature collagen growth. This study was designed to demonstrate the positive results of Gln on injury in corrosive esophagitis. Method: Thirty Sprague-Dawley rats were used in the study. They were divided into 3 groups. CE was formed by dripping 20% sodium hydroxide into the distal esophagus in both groups except the control group (n=10). First group (n=9) was left untreated, while the other group (n=9) was fed orally with the addition of 1 g/kg Gln once a day for 21 days. All rats were sacrificed after 3 weeks. Esophagus of treated and other group rats were examined under light microscope to evaluate collagen deposition, histological damage score and stenosis index. Results: Excess submucosal collagen, muscularis mucosal damage, inflammation and ulceration, which are among the histological damage score parameters, were significantly higher in the untreated group than in the Gln group (p=0.005, p=0.015, p=0.001, respectively). The stenosis index was significantly different (p=0.013). The group treated with Gln had inflammation but no ulceration and necrosis. Conclusion: Our experimental animal study suggests that Gln in nutrition reduces damage in the esophageal mucosa, slows down or partially stops the cellular destruction process that causes stenosis.